Engineering Education Management for Sustainable Development through Globalization, Diversity and Inclusion – A Curriculum Perspective - Das, Bhagwan; Agbinya, Johnson I; Lohana, Sonia; Gyasi-Agyei, Amoakoh; Mahdi, Osama A.; Al-Quraishi, Tahsien; Alazab, Ammar (Proceedings of International Conference for ICT (ICICT) - Zambia, 2023)
In this paper, the conceptual framework is presented for Engineering Education Management based on Sustainable Development through Globalization, Diversity, and Inclusion. The framework will be helpful to revise and improve the existing curriculum for engineering students. Nowadays, globalization, diversity, and inclusion have had a significant impact on teaching and learning in the engineering curriculum. Their impact stimulates a broad perspective, cultural competence, and collaborative problem-solving skills that are vital for engineers working in an increasingly interconnected and diverse world. The paper discussed the various aspects of how Globalization, Diversity and Inclusion can be helpful to improve teaching and learning in the engineering curriculum. Our main contribution for this work is that we have proposed a methodology to bring Globalization, Diversity, and Inclusion in engineering education.